2020
DOI: 10.3390/brainsci10080531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Electrical Stimulation on Human Auditory Processing and Behavior—A Review

Abstract: Transcranial electrical stimulation (tES) can adjust the membrane potential by applying a weak current on the scalp to change the related nerve activity. In recent years, tES has proven its value in studying the neural processes involved in human behavior. The study of central auditory processes focuses on the analysis of behavioral phenomena, including sound localization, auditory pattern recognition, and auditory discrimination. To our knowledge, studies on the application of tES in the field of hearing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 122 publications
0
17
0
Order By: Relevance
“…These studies found that the tACS did modulate speech comprehension, but that the best and worst phase shifts were highly variable between subjects (Riecke et al, 2018;Zoefel, Archer-Boyd and Davis, 2018). Similarly, related work on temporal delays between the sound and the neurostimulation waveform found large variability between subjects, and in one case no significant effect on the population level (Riecke et al, 2018;Wilsch et al, 2018;Erkens et al, 2020;Wang et al, 2020). In our previous work on the role of phase shifts in tACS with the speech envelope we employed, as in this study, natural speech in which syllables did not occur at a single fixed frequency and found a phase dependency of the resulting speech comprehension that was largely consistent across the different subjects.…”
mentioning
confidence: 90%
“…These studies found that the tACS did modulate speech comprehension, but that the best and worst phase shifts were highly variable between subjects (Riecke et al, 2018;Zoefel, Archer-Boyd and Davis, 2018). Similarly, related work on temporal delays between the sound and the neurostimulation waveform found large variability between subjects, and in one case no significant effect on the population level (Riecke et al, 2018;Wilsch et al, 2018;Erkens et al, 2020;Wang et al, 2020). In our previous work on the role of phase shifts in tACS with the speech envelope we employed, as in this study, natural speech in which syllables did not occur at a single fixed frequency and found a phase dependency of the resulting speech comprehension that was largely consistent across the different subjects.…”
mentioning
confidence: 90%
“…Each subject would undergo these three stimulation protocols in a randomized order. Meanwhile, the stimulation conditions were performed with a wash-off period of at least one week between each other [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 12, 2021. ; https://doi.org/10.1101/2021.04.12.439458 doi: bioRxiv preprint worst phase shifts were highly variable between subjects (Riecke et al, 2018;Zoefel, Archer-Boyd and Davis, 2018). Similarly, related work on temporal delays between the sound and the neurostimulation waveform found large variability between subjects, and in one case no significant effect on the population level (Riecke et al, 2018;Wilsch et al, 2018;Erkens et al, 2020;Wang et al, 2020). In our previous work on the role of phase shifts in tACS with the speech envelope we employed, as in this study, natural speech in which syllables did not occur at a single fixed frequency and found a phase dependency of the resulting speech comprehension that was largely consistent across the different subjects.…”
Section: Multiple Linear Regressionmentioning
confidence: 99%